A Radio Transmitter for Quail - Lorvel J. Shields; B. S. Mueller (National Quail Symposium Proceedings, 2017)
This paper describes a small radio-transmitter that has been developed specifically for use on quail. The transmitter weighs 5g, is disk-shaped (25mm diameter X 7mm thick) and is worn on the chest. It is kept in place by a harness made from nylon covered, stainless-steel wire that also functions as the antenna. Because of the transmitter's light weight, shape, and position, quail seem to tolerate it very well. Also, it cannot be seen by aerial predators. The nominal signal consists of 30 msec pulses with a frequency of 1 ha. Movement produces one extra 40 rnsec pulse per cycle, 500 msec after the 30 msec pulse. These characteristics allow for relatively simple automatic detection and recording of activity. The transmission range, using a commercially available 3-element Yagi and receiver, exceeds one-half mile. Life expectancy is about 60 days. Components for the transmitter cost about 25.00 (1981).